Whither the LMS : Is the LMS Still Fit for Purpose? - Willems, Julie; Huijser, Henk; Doherty, Iain; Soong, Alan (Journal of University Teaching & Learning Practice v.20 n.6 https://doi.org/10.53761/1.20.6.13, 2023)
Learning management systems (LMSs) have long been adopted by tertiary education providers to be the conduit through which courses are delivered. However, debates about the capacity of the LMS to meet all the required current and future needs of both students and educators have become more pronounced over the past few years, particularly given the rapid shift to online learning during Covid-19. This qualitative study aimed to examine practitioners' current experiences in using the LMS for formal teaching and learning in tertiary environments. To discern the possibilities and issues, a focus group was held with fourteen practitioners from Australasia (Australia and Singapore), Canada, and the UK (England and Scotland) attending virtually. Adopting a novel and recognised approach to thematic analysis, a Delphi process was adopted on the de-identified webinar and chat transcripts. Analysis revealed several key themes ranging across pedagogical, technological, and managerial issues with the LMS. The findings in this paper have become even more pertinent as a result of Covid-19 with institutions urgently reviewing standards for teaching in the LMS whilst also reviewing their overall technology ecosystems to ensure a suite of complementary teaching and learning tools to enable best teaching and learning practices. It appears the LMS still has a key role to play in contemporary learning ecosystems. [Author abstract]